2021
DOI: 10.51201/jusst12683
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Resource Management Practices and Job Satisfaction on Employee Performance in the Ministry of Foreign Affairs of Kuwait

Abstract: The current study aims to examine the human resource management practices and job satisfaction on employee performance and examine the mediating role of job satisfaction in the ministry of foreign affairs of Kuwait. The survey included 212 employees are working in the ministry of foreign affairs of Kuwait. The results of this study indicated that human resource management practices have a positive direct effect on employee performance. Moreover, the results of this study indicated that human resource managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of this study are in line with the results of research by Pradhan et al (2019), Alsafadi & Altahat (2021), Almutairi &Arabiat (2021), andEmilisa (2023), which found that there is a positive and significant effect of human resource practices on job satisfaction.…”
Section: The Effect Of Human Resource Practices On Job Satisfactionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are in line with the results of research by Pradhan et al (2019), Alsafadi & Altahat (2021), Almutairi &Arabiat (2021), andEmilisa (2023), which found that there is a positive and significant effect of human resource practices on job satisfaction.…”
Section: The Effect Of Human Resource Practices On Job Satisfactionsupporting
confidence: 91%
“…A number of research results conclude that psychological empowerment has an influence on job satisfaction (Singh & Singh, 2019;Qing et al, 2019;Maan et al, 2020, Alagarsamy et al, 2020. Another variable that can affect job satisfaction is human resource practices (Hewagama et al, 2019;Pradhan et al, 2019;Alsafadi & Altahat, 2021;Almutairi & Arabiat, 2021;Emilisa, 2023). Apart from psychological empowerment and human resource practices, there are other variables that influence job satisfaction, namely employee engagement (Alagarsamy et al, 2020;Humayon, 2022;Nguyen & Ha, 2023;Ibrahim et al, 2023).…”
Section: Issn : 2615-537 (Online)mentioning
confidence: 99%
“…Employee job performance is crucial in the public sector as it directly impacts the quality of services provided and the overall performance of the government (Ahmad et al, 2020). The performance of employees in the public sector directly impacts the efficiency and effectiveness of public service delivery (Almutairi and Arabiat, 2021). Public sector employees play a pivotal role in delivering exceptional public services, and implementing individual-level measures can improve overall organizational performance (Johari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%